Lower FOXP3 mRNA Expression in First-Trimester Decidual Tissue from Uncomplicated Term Pregnancies with a Male Fetus - Tom E. C. Kieffer; Anne Laskewitz; Marijke M. Faas; Sicco A. Scherjon; Jan Jaap H. M. Erwich; Sanne J. Gordijn; Jelmer R. Prins (Journal of Immunology Research)
Pregnancies with a male fetus are associated with higher risks of pregnancy complications through maladaptation of the maternal immune system. The pathophysiology of this phenomenon is unknown. A possible pathway could be a fetal sex-dependent maternal immune response, since males have a Y chromosome encoding specific allogenic proteins, possibly contributing to a different response and higher complication risks. To analyze whether fetal sex affects mRNA expression of maternal immune genes in early pregnancy, real-time PCR quantification was performed in the decidual tissue from primigravid pregnancies (n=20) between 10 and 12 weeks with uncomplicated term outcomes. Early-pregnancy decidual mRNA expression of the regulatory T-cell marker, FOXP3, was sixfold lower (p<0.01) in pregnancies with a male fetus compared to pregnancies with a female fetus. Additionally, mRNA expression of IFNγ was sixfold (p<0.05) lower in pregnancies with a male fetus. The present data imply maternal immunologic differences between pregnancies with male and female fetuses which could be involved in different pregnancy pathophysiologic outcomes. Moreover, this study indicates that researchers in reproductive immunology should always consider fetal sex bias.